Sistem Ekonomi Islam Solusi Perekonomian Indonesia - Abd Aziz (Fakultas Ekonomi dan Bisnis Islam, 2016)
Islamic economics being developed at this time both the level of theory and practice and it is a concrete manifestation of the efforts of the operationalization of Islam as a religion rahmatan lil ‘alamin, through a long process and will continue to evolve with the times. Muslim thinkers steeped in the Islamic economy is also up to now there has been no unified view of constructing theory of Islamic economics. There are differences of interpretation, approaches and metedologi built in shaping the concept of Islamic economics. This is because of differences in educational background, skills, and experience that is owned. Referring to the opinion Aslem Haneef, an Islamic economic thinkers Malaysia, Muslim thinkers in economics are grouped into three categories: First, experts fiqh or Islamic law so that the approach is legalistic and normative. Second, the modernist group bolder in their interpretation of the teachings of Islam in order to address problems faced by contemporary society. Third, practitioners or Muslim economists that berlatang belaknhg western education. They try to combine the approaches of jurisprudence and economics so that the Islamic economy terkonseptualisi be integrated with laiun said they were trying to construct an Islamic economy such as economic konvensioanal, but by reducing the values are not in line with Islam and give Islamic values in economic analysis.